Microstructural Analysis of Corrosion Mechanisms in Rotary Rings of Calcining Furnaces Used in Soda Ash Production - Meng, Qinghua; Cao, Ning (Archives of Metallurgy and Materials, 2026)
Severe surface corrosion of riding rings in rotary steam calcining furnaces commonly occurs during soda ash production, threatening operational stability and increasing maintenance costs. In this study, forged 35CrMo steel riding rings were investigated to clarify their corrosion behaviour and mechanisms. Environmental media analysis combined with hardness testing, metallographic observation, chemical composition analysis, and SEM-EDS characterisation was employed to examine microstructural evolution, corrosion morphology, and mechanical degradation. The results demonstrate that the corrosion is governed by the synergistic action of electrochemical corrosion in an alkaline dust environment, hydraulic shock caused by lubricant entrapment, and alternating compressive stresses during operation. Pronounced iron oxide formation, severe surface damage, and significant hardness reduction were observed in corroded regions. This study elucidates the coupled corrosion mechanisms of riding rings and provides guidance for lubrication optimisation and service life extension of critical components.